BANK OWNERSHIP, MODE OF ENTRY, AND CREDIT ALLOCATION TO MSMEs - Setiawan, Rahmat; Putri, Octavia Reniar; Jafar, Rosmiati (TRIKONOMIKA, 2021)
Micro, small, and medium enterprises (MSMEs) have strategic roles in economic structure, especially in developing countries, so, they need supports from the banking industry, including foreign banks, by giving loans they need. This study aims to find the effect of bank ownership and mode of entry on credit allocation to MSMEs. We use 110 samples of conventional commercial banks and 41 samples of foreign-owned banks in Indonesia during 2010-2017, with 686 and 266 observations. The results of multiple regression show that banks with government ownership have higher credit allocation to MSMEs than non-government ownership and banks with foreign ownership have lower credit allocation to MSMEs than domestic ownership. Based on their mode of entry, banks with foreign ownership via greenfield have lower credit allocation to MSMEs than via takeover.